Brazil : Report on the Observance of Standards and Codes--Accounting and Auditing - World Bank (Washington, DC, 2014)
This Report on the Observance of Standards and Codes: Accounting and Auditing (ROSC A&A) has been prepared under the Financial Sector Assessment Program in Brazil. The report assesses the status of implementation of 2005 ROSC A&A policy recommendations, highlights recent improvements in Brazil's corporate financial reporting framework, and sheds light on emerging issues regarding the institutional underpinnings of accounting and auditing practices that require further upgrading in line with international good practices. In addition to maintaining appropriate macroeconomic policies, there is an extensive agenda to implement wide ranging structural reforms to promote growth, increase productivity, and raise living standards. Brazil's low domestic savings and limited domestic long-term financing markets remain a major impediment to the investment in infrastructure that is required to sustain high economic growth. Given the increased role played by the financial system, especially as more families and businesses have access to banking credit and capital markets, it will also be necessary to further develop and strengthen Brazil's financial markets and institutions, to help to ensure macroeconomic stability and sustainable growth. In this context, one of the strategic objectives of the ROSC A&A is to help consolidate the institutional framework for accounting and auditing in Brazil in order to support improvements in business conditions in general, and facilitate access to more abundant and cheaper domestic and foreign financial resources.